Collisional unfolding of multiprotein complexes reveals cooperative stabilization upon ligand binding - Niu, Shuai (Protein Sci, 2015)
Cooperative binding mechanisms are a common feature in biology, enabling a diverse range of protein-based molecular machines to regulate activities ranging from oxygen uptake to cellular membrane transport. Much, however, is not known about such cooperative binding mechanisms, including how such events typically add to the overall stability of such protein systems. Measurements of such cooperative stabilization events are challenging, as they require the separation and resolution of individual protein complex bound states within a mixture of potential stoichiometries to individually assess protein stabilities. Here, we report ion mobility-mass spectrometry results for the concanavalin A tetramer bound to a range of polysaccharide ligands. We use collision induced unfolding, a relatively new methodology that functions as a gas-phase analog of calorimetry experiments in solution, to individually assess the stabilities of concanavalin A bound states. By comparing the differences in activation voltage required to unfold different concanavalin A–ligand stoichiometries, we find evidence suggesting a cooperative stabilization of concanavalin A occurs upon binding most carbohydrate ligands. We critically evaluate this observation by assessing a broad range of ligands, evaluating the unfolding properties of multiple protein charge states, and by comparing our gas-phase results with those obtained from calorimetry experiments carried out in solution.